Strengthening National Character in Islamic Elementary School - Zulfikar, Gilang; Permady, Gigieh Cahya; Sudirman, Albertus (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
education in schools, including the learning process in the classroom. This has been seen in Indonesia's national education goals that intellectual intelligence, emotional intelligence, and spiritual intelligence assessment in a proportional position. Therefore, the purpose of this research is to see how far strengthening national character is applied to students, especially at Galudra Elementary School. This type of research approach uses qualitative methods with a library research approach. The value of the nation's educational character is referred to in research data., and the data source is class II MI. Thematic books that employ data collection techniques are documentation, and data analysis is content analysis. The results of this study indicate that the strengthening of national character in Madrasah Ibtidaiyah is contained in thematic books, especially on the learning theme of PPKn MI/SD class II, semester 1 of the 2013 curriculum. That is done through 1) starting a discussion of knowledge material, 2) after discussing knowledge material, 3) on pictures/stories specifically for attitude development, and on attitude assessment. Then the national character contained in the class 2 thematic book of MIS Galudra includes the characters: Religious, respect and appreciation, discipline, independence, democracy, social care, love for the motherland, defending the country, responsibility, friendship, and tolerance.